2007
DOI: 10.1086/517493
|View full text |Cite
|
Sign up to set email alerts
|

Proper Motions of the Jets in the Region of HH 30 and HL/XZ Tau: Evidence for a Binary Exciting Source of the HH 30 Jet

Abstract: We present [S ii] images of the HH 30 and HL/XZ Tau region obtained at two epochs, as well as long-slit optical spectroscopy of the HH 30 jet. We measured proper motions of $100Y300 km s À1 for the HH 30 jet and counterjet and of $120 km s À1 for the HL Tau jet. Inclination angles with respect to the plane of the sky are 0 Y40 for the HH 30 jet and 60 for the HLTau jet. Comparison with previous observations suggests that most of the jet knots consist of persistent structures. Also, we corroborate that the HH 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(157 citation statements)
references
References 37 publications
16
138
3
Order By: Relevance
“…The present PM values are more similar to the results of Anglada et al (2007) than to the higher estimates of Mundt et al (1990) and Movsessian et al (2007). Very probably this discrepancy results from the unavoidable systematic errors of various origin, which were briefly discussed also in Sect.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The present PM values are more similar to the results of Anglada et al (2007) than to the higher estimates of Mundt et al (1990) and Movsessian et al (2007). Very probably this discrepancy results from the unavoidable systematic errors of various origin, which were briefly discussed also in Sect.…”
Section: Resultssupporting
confidence: 86%
“…In addition, these knots also demonstrate perceptible proper motions, which were first studied by Mundt et al (1990). Other data, presented in the papers of Movsessian et al (2007) and Anglada et al (2007), showed a certain difference between the proper motions (PM) of the knots, obtained in Hα and [S ii] emission lines. A&A 541, A16 (2012) There are various theoretical approaches to explain the formation of knotty structures in the jets .…”
Section: Introductionmentioning
confidence: 94%
“…Most research has been conducted in the optical and NIR band including photometry, polarimetry, medium-resolution imaging and high-resolution spectroscopy with ground-based instruments (Vrba et al 1985;Appenzeller et al 2005;Anglada et al 2007) and high-resolution imaging with the Hubble Space Telescope (HST) from outside the atmosphere (B96; C01;Watson & Stapelfeldt 2004, hereafter W04). The SED in the MIR has been measured with ISOCAM/ISO (Stapelfeldt & Moneti 1999;Brandner et al 2000) and refined substantially by observations with IRS on the Spitzer Space Telescope (SST, Furlan et al 2008).…”
Section: Observationsmentioning
confidence: 99%
“…Effective temperature and luminosity are consistent with a contracting protostar of spectral class M3 ± 2 with R * ∼ 2 R (Simon et al 2000), but it is very difficult to constrain the properties of the central source and a binary, as proposed by Anglada et al (2007) and G08, seems a viable option.…”
Section: Fitting Of the Sedmentioning
confidence: 99%
See 1 more Smart Citation